ANALISIS FAKTOR ELEKTRONIK WORD OF MOUTH (EWOM) DALAM MEMPENGARUHI KEPUTUSAN BERKUNJUNG WISATAWAN - Humaira, Aulian; Wibowo, Lili Adi (Universitas Pendidikan Indonesia, 2016)
It has been acknowledged that tourism is a dynamic sector which is staying at a big competition globally. More countries around the world are competing to develop the tourism potential to be well-known. Asian Pasific region has high commitment to win the global tourism competition, proved by the average calculation of tourist visits, which is dominated by Asian Pasific than other regions. Malaysia is the only country in South East Asian which counted in The World’s Top Destination. It has many tourism destinations. One of them is Langkawi Island that is a well-known and popular tourism destination which successfully achieved a lot of awards. The visit growth in Langkawi Island has instability, and the most decreasing growth appeared in 2007 to 2009 amount of 1, 3% and followed by 2, 5% from 2009 to 2010. The decrease was caused by the lower visit intention of tourist or to be called as future behavioral intention. Visit decision is motivated by push and pull factors, which come from the internal of tourist as well as the external factors of tourism destination. The strategy by Langkawi Island authority to increase the visit decision is by implementing electronic word of mouth (EWOM) which shared through social media. EWOM consists of tie strength, homophile, trust, normative influence and informative influence. This research used descriptive and verified method. The respondents are tourists of Langkawi Island with the number of sample 100 tourists. This research is using Partial Least Square (PLS) analyzing technique. Independent variable is electronic word of mouth with its dimensions are tie strength (X1), homophile (X2), trust (X3), normative influence (X4), and informative influence (X5). Furthermore, the tourist visit decision is the dependent variable (Y). The result shows that EWOM factors are placed in high category whereas it has a weak positive impact upon the tourist's visit decision in Langkawi Island, Malaysia. PLS result shows that the dominant factors of EWOM are homophile and normative influence. Meanwhile, the impact of EWOM to the tourist visit decision is 0,284 and the residue by other factors, which is not studied for this research.